Repositioning TVET for Economic and Industrial Growth in Nigeria - Okoli, Johnpaul Chisom; Agada, Micaiah Enyo-Ojo (Journal of Research in Industrial Technology and Educational Studies, 2025)
Technical and Vocational Education and Training is designed to equip individuals with practical skills and knowledge for employment in various technical and vocational fields. TVET aims to prepare individuals for specific occupations and trades, contributing to both their personal economic advancement and the overall economic development of a country. In Nigeria, emphasis on technology integration, personalized learning, and industry collaboration which includes using virtual reality (VR) and augmented reality (AR) for simulations, online learning platforms, and data analytics for tailoring instruction have dominated TVET trends. The role and importance of TVET in National development cannot be over emphasized, this is because Technical and Vocational Education and Training provides the necessary knowledge, attitude and competencies for survival and sustainable national development till to today. The challenges and issues of TVET in Nigeria over the years make it difficult to fully tap these obvious TVET benefits. The paper proffer Solutions to the emerging challenges and recommendations to the Repositioning of TVET for Economic and Industrial Growth in Nigeria if positively met, will enhance the national development, economic growth and technological advancement in Nigeria.